Accuracy and reproducibility of ambient topographies at the nanoscale by AFM: Several months of metrological monitoring - Gharibeh Ziad; Leménager Maxime; Bousbia Hind; Coq Germanicus Rosine (EPJ Web of Conferences)
With the high integration of microelectronic devices, nanoscale surface characterization is critical to process development. The widely used atomic force microscopy provides 2D characterization of the surface at the nanoscale. In this paper, a statistical study of the topographic mode PeakForce Tapping mode is performed. A silicon calibration sample with structures of 20 nm, is characterized, and from 28 days of measurements at the same location, data processing and analysis is proposed to determine the reproducibility of the height measured by AFM. From the section analysis, an uncertainty of 0.26 nm in air is determined. Statistical analysis is also used, and the mode is applied to characterize a dielectric material on the top of a highly integrated capacitor.